General anesthesia versus local anesthesia for endovascular aortic aneurysm repair. Issue 32 (August 2018) - Noh, Minsu; Choi, Byung-Moon; Kwon, Hyunwook; Han, Youngjin; Ko, Gi-Young; Kwon, Tae-Won; Noh, Gyu-Jeong; Cho, Yong-Pil
Abstract : Abstract: The aim of this study was to compare general and local anesthesia techniques in patients treated with elective endovascular aortic aneurysm repair (EVAR) for infrarenal aortic aneurysms. In this single-center, observational cohort study, in all, 259 consecutive patients who underwent elective EVAR was included; 144 patients (55.6%, 126 men, mean age 72.8 years) operated on under general anesthesia (GA group) and 115 (44.4%, 100 men, mean age 72.3 years) operated on under local anesthesia (LA group). A retrospective analysis regarding technical feasibility, endoleaks, length of hospital stay, and 30-day clinical outcomes was performed. There was no anesthetic conversion (from LA to GA) during EVAR, and no significant difference was noted in the incidence of endoleaks and its types in relation to anesthetic techniques on final completion angiograms (14.1% vs 18.4%; P  = .347) and follow-up computed tomography angiogram at 30 days after EVAR (23.6% vs 19.1%; P  = .384). Significant differences were not observed with regard to a prolonged length of hospital stay in relation to anesthetic techniques (8.6 ± 16.3 vs 7.2 ± 3.3; P  = .348), and the main outcomes showed no significant differences in morbidity (20.1% vs 16.5%; P  = .457), mortality (0.0% vs 0.0%), and the rates of secondary therapeutic procedures (9.7% vs 4.3%; P  = .099) between the 2 groups during the 30-day follow-up. We have not shown a definite difference in 30-day outcomes between GA and LA for EVAR. The anesthetist and surgeon, in consultation with the patient, should decide which anesthetic technique to use on an individual basis.